2016
DOI: 10.1517/14740338.2016.1167186
|View full text |Cite
|
Sign up to set email alerts
|

The safety of monoclonal antibodies for treatment of colorectal cancer

Abstract: The most common toxicities associated with the VEGF-A directed antibody bevacizumab are hypertension, proteinuria, thromboembolism, bleeding, gastrointestinal perforation and prolonged wound healing. Similarly, the rate of hypertension and proteinuria is increased during treatment with the VEGFR2 antibody ramucirumab. On the other hand the most frequent side effects of EGFR targeted antibodies are skin rash, hypersensitivity reactions and hypomagnesemia. Due to the murine portions of cetuximab the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…As an off label use, Bevacizumab is applied intravitreally to treat age related macular degeneration with good clinical outcome and good safety [27,28]. The most common adverse events associated with systemically applied Bevacizumab in humans are hypertension, proteinuria, thromboembolism, bleeding, gastrointestinal perforation and prolonged wound healing [29]. Importantly, while potential systemic side effects were not explicitly addressed in our study, signs of intolerance or changed behavioral signs were not observed in any of the Bevacizumab treated animals within the period tested.…”
Section: Discussionmentioning
confidence: 99%
“…As an off label use, Bevacizumab is applied intravitreally to treat age related macular degeneration with good clinical outcome and good safety [27,28]. The most common adverse events associated with systemically applied Bevacizumab in humans are hypertension, proteinuria, thromboembolism, bleeding, gastrointestinal perforation and prolonged wound healing [29]. Importantly, while potential systemic side effects were not explicitly addressed in our study, signs of intolerance or changed behavioral signs were not observed in any of the Bevacizumab treated animals within the period tested.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is the fourth leading cause of cancer-related death worldwide. With the addition of biologicals to 5-fluorouracil (5-FU)-based treatment regimens, the outcome of metastatic colorectal cancer (mCRC) patients has markedly improved during the last decade (1). However, to further optimize treatment, new effective drugs are highly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has found that anti-EGFR therapy can cause infusion-related reactions and skin alterations 39. Moreover, anti-VEGF therapy can cause arterial hypertension, venous and arterial thromboembolic events, and gastrointestinal perforations 40. Our meta-analysis indicated that, in the anti-EGFR group, there was a significant increase in Grade 3 toxicity or lower, including skin disorders, hypomagnesemia, and hypokalemia, whereas the patients in the anti-VEGF group experienced hypertension more often.…”
Section: Discussionmentioning
confidence: 98%